Study of the Presence of Streptococcosis in Tilapia Cultivation in Banyumas Regency - Saputra, Kukuh Andre Setya; Purbomartono, Cahyono; Pratama, Ikhsan; Mulia, Dini Siswani; Rijal, Muhammad Azharul (Study Program of Aquaculture, Department of Fisheries and Marine Science, Faculty of Agriculture, University of Mataram, 2026)
Tilapia is the most widely cultivated fish in Banyumas which is susceptible to bacterial diseases caused by the increasing number of disease cases in tilapia (Oreochromis niloticus) due to high cultivation intensification. One of the diseases that often attacks is streptococcosis caused by the bacteria Streptococcus sp., which can cause mass mortality and major economic losses for farmers. The purpose of this study was to identify pathogenic bacteria in farmed tilapia in Banyumas. The method used in this study was a purposive sampling method, namely by taking samples of tilapia that have characteristics of disease symptoms such as protruding eyes, damaged fins, and red wounds on the scales from three locations, namely Beji Village, Karangsalam Village, and Pasir Wetan Village. Bacterial samples were obtained from four organs, namely the brain, kidneys, eyes, and liver, then observed the morphology of bacterial colonies and Gram KOH tests were carried out. The results showed that bacterial colonies found in most organs were round to irregular in shape, white to yellowish in color, and Gram positive, which shows the characteristics of Streptococcus sp. bacteria. Based on these results, it can be concluded that Streptococcus sp. bacteria are still the main threat in tilapia cultivation in Banyumas, so it is necessary to take preventive measures through the implementation of good biosecurity, the use of immunostimulants, and the development of vaccines to maintain the sustainability of tilapia cultivation businesses, especially in Banyumas Regency.